Prenatal Diagnosis of Holt–Oram Syndrome With a Novel Mutation of TBX5 Gene: A Case Report - He, Guan-nan; Wang, Xue-yan; Kang, Min; Chen, Xi-min; Xi, Na; Zhao, Jing; Chen, Xi (Frontiers in Pediatrics, 2021)
Background: Holt–Oram syndrome (HOS) is an autosomal dominant disorder caused by mutations of TBX5 gene. Case presentation: We report a fetus with HOS diagnosed sonographically at 23 weeks of gestation. The fetal parents are non-consanguineous. The fetus exhibited short radius and ulna, inability to supinate the hands, absence of the right thumb, and heart ventricular septal defect (VSD), while the fetal father exhibited VSD and short radius and ulna only. Fetal brother had cubitus valgus and thumb adduction, except for VSD, short radius and ulna. The pregnancy was terminated. Whole-exome sequencing (WES) revealed a novel mutation in the TBX5 (c.510+1G>A) in the fetus inherited from the father. The variant (c.510+1G>A) occurs at splice donor and may alter TBX5 gene function by impact on splicing. It was not previously reported in China. Conclusion: Our case reported a novel mutation in TBX5, which expanded the known genetic variants associated with HOS.